Tolerance Education Towards Diversity of People in Schoolls - Al Hadi, Abil Fida Muhammad Qois; Maksum, Muh. Nur Rochim; Rohmat, Cecep Sobar (Iseedu: Journal of Islamic Educational Thoughts and Practices, 2024)
The role of education in fostering a tolerant attitude among society is to instill a tolerant attitude towards religious life in students. Religious diversity is often seen as causing conflict between majority groups versus minority groups. However, the religious diversity found in most schools does not cause conflict due to differences in religious backgrounds. The aim is to identify forms of religious tolerance in schools and examples of implementing tolerance among students. Carrying out religious activities in order to build tolerance between believers. The nature of religious tolerance between religious communities which is applied to the practice of other religious activities is considered effective, because apart from providing basic religious teachings, students also receive them directly. Continue to recognize the practical realities of establishing communication relationships with followers of other religions. Religion is often the source of all problems, but it is also a material factor in overcoming problems that arise in society. So then, there is an urgent need to understand this condition using relevant methods. And in this discussion, the approach used includes a sociological approach. The sociological approach is an approach or method. The discussion revolves around the communal object in the discussion. This approach is an approach that enlightens people who are experiencing problems. Therefore, a sociological (society) approach is needed to understand what they believe based on their religious knowledge.